Notes on genus Cybister Curtis, 1827 (Coleoptera: Dytiscidae) with the first records of Cybister danxiaensis Zhuo-Yin Jiang and Cybister convexus Sharp from Vietnam - Nguyen, Quang Cuong; Nguyen, Thanh Manh; Phan, Thi Giang; Sergey, Ryndevich; Truong, Xuan Lam (Academia Journal of Biology, 2024)
The genus Cybister Curtis, 1827 is reviewed for the fauna of Vietnam. The 5 species are diagnosed with illustrated habitus, leg, and male genitalia. Additional measurement data, and an updated identification key for all species are provided. Two species Cybister convexus Sharp, 1882, and Cybister danxiaensis Zhuo-Yin Jiang, 2023, are recorded for the first time in Vietnam.